Pembuatan Mobile Learning untuk Ibu Mengenali dan Mengatasi Permasalahan Anak Usia Dini Sulit Makan Menggunakan Metode Waterfall - Rian Farta Wijaya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The research aims to develop a mobile learning app for mothers to help them identify and solve early childhood problems that are difficult to eat. The development method used is the Waterfall method, which involves structured stages such as needs analysis, planning, implementation, testing, and maintenance. At the need analysis stage, we conducted surveys and interviews with mothers who had early childhood to understand the challenges they faced in dealing with their children's eating problems. Next, at the design stage, we design an application interface, educational content, and interactive features that will help you understand this issue better. Application deployment involves software development based on the design that has been made. After that, we tested the application to ensure its functionality and effectiveness in helping mothers identify and deal with early childhood eating problems. We also involved moms as test users during this phase to get valuable feedback. The results of this study show that the use of the Waterfall method in the development of Mobile Learning for early childhood problems that are difficult to eat produces applications that can help mothers significantly. The application provides relevant information, practical advice, and community support for mothers facing this problem. In conclusion, the Waterfall method has proven to be effective in producing mobile learning applications that are useful to mothers in dealing with early childhood feeding problems. The app has the potential to enhance mother's understanding of their children's nutrition and provide better solutions to dealing with eating problems in early childhood.